APOE, PCSK9, and CETP genetic variants as potential biomarkers of dyslipidaemia in black South Africans with Type 2 Diabetes Mellitus - Evans, Jonathan (Division of Human Genetics, 2019)
Dyslipidaemia is a commonly encountered clinical condition and is a major risk factor for cardiovascular diseases. Although there are many factors associated with dyslipidaemia, a strong genetic component is evident. Apolipoprotein E (APOE), proprotein convertase subtilisin/kexin type 9 (PCSK9), and cholesteryl ester transfer protein (CETP) are key regulators of plasma cholesterol levels. Thus, genetic variation in the genes coding for these proteins contributes to dyslipidaemia. In this study, a cohort of black South African Type 2 Diabetes Mellitus (T2DM) patients was characterized for mutations in genes coding for APOE, PCSK9, and CETP, and the possible effects of these variants on their lipid profiles was evaluated. Participants (n=417) were recruited from the Chris Hani Baragwaneth Hospital Diabetes Clinic, Johannesburg from whom blood samples were obtained for DNA extraction. The cohort was further stratified into two groups; individuals on statin treatment (Sim+, n=291), and the second that was not on treatment (Sim-, n=87). Lipid profiles were determined by enzymatic methods. DNA was genotyped for APOE, PCSK9, and CETP variants using PCRRFLP and Sanger sequencing. Analysis of the effects of the genetic variants was carried out in two ways. Firstly, for all the participants combined, and then by separating those on statin treatment from those without (Sim+ vs. Sim-). Genotype and allele frequencies were calculated followed by genotype-phenotype correlations with lipid profiles. Univariate analysis showed a significant association between the APOE4 isoform and lower HDL-c levels in the combined cohort (p=0.034). The effects were more pronounced in the Sim- group (p=0.004) but were absent in the Sim+ group. Contrary to above, APOE2 was significantly associated with lower total cholesterol (TC) (p< 0.001) and lower LDL-c (p< 0.001) when compared to APOE3 in the combined cohort. Upon analysing treatment groups, the correlations were observed in the Sim+ group (p=0.027 and p=0.003, respectively), while there were no observed correlations in the Sim- group. The CETP rs34065661C/G and G/G genotypes were significantly associated with increased HDL-c levels (p=0.017; when applying a dominant genetic model) in the combined cohort, as well as in the Sim+ group (p=0.026). Multivariate analysis, using a generalized linear model, confirmed associations between APOE rs429358C and lower HDL-c (OR=0.881, p=1.64e04), and APOE rs7412T and decreased LDL-c (OR=0.759, p=0.012). No significant associations were observed for PCSK9 polymorphisms. We report significant associations between APOE and CETP genetic variations and altered lipid levels in this black South African T2DM population. These genetic variants could be biomarkers for dyslipidaemia among Africans. However, it is imperative that the APOE, PCSK9, and CETP genes are fully characterized for additional polymorphisms in order to come up with a better genetic profile that explains the variance in lipid levels observed in the black South African population. The impact of these genetic variants could be relevant to other black African populations as well.